Circular RNA hsa-circ-0005238 enhances trophoblast migration, invasion and suppresses apoptosis via the miR-370-3p/CDC25B axis - Huang, Zhuomin; Zhu, Litong; Zhang, Quanfu; Zhao, Depeng; Yao, Jilong (Frontiers in Medicine, 2022)
Background: Fetal growth restriction (FGR) is attributed to various maternal, fetal and placental factors. Trophoblasts participate in the establishment and maintenance of pregnancy from implantation and placentation to providing nutrition to fetus. Studies have reported that impaired trophoblast invasion and proliferation are among factors driving development of FGR. Circular RNAs (circRNAs) can regulate trophoblast function. We assessed the significance of circRNAs underlying FGR development. Methods: Next generation sequencing (NGS) was carried out to quantify levels of circRNAs in placenta tissues with and without FGR. In vitro experiments including transfection, MTS assays, flow cytometry analyses, Transwell assays, wound healing assays, western blotting, qRT-PCR, dual-luciferase assays, immunofluorescence staining, and RIP assay were performed. Results: There were 18 differentially expressed circRNAs between FGR placentas and uncomplicated pregnancies, while levels of hsa-circ-0005238 were markedly low in FGR placentas. Our in vitro experiments further revealed that hsa-circ-0005238 suppressed apoptosis and enhanced proliferation, migration, invasion of trophoblast cell lines. The hsa-miR-370-3p was identified as a direct target of hsa-circ-0005238. Mechanistically, hsa-miR-370-3p prevents invasion as well as migration of trophoblast cells by downregulating CDC25B. Conclusions: The hsa-circ-0005238 modulates FGR pathogenesis by inhibiting trophoblast cell invasion and migration through sponging hsa-miR-370-3p. Hence, targeting this circRNA may be an attractive strategy for FGR treatment.